Gender differences and commuting accidents in Italy: INAIL Data Base analysis on fatalities (2009-2013) - Giliberti, Claudia; Salerno, Silvana (La Medicina del Lavoro, 2016)
Background: Commuting accidents represent the leading cause of work-related fatalities among women in Italy. For working women, the journey from home to work is the most dangerous part of the day. Objectives: Analysis of data on fatal commuting accidents in order to identify risk factors among women. Methods: INAIL Statistical Data (2009-2013) related to fatal commuting were analyzed by gender, age, immigration, activities, geographical area, working time, month and day of the week. Results: Italian and immigrant women die mainly from commuting accidents (207 cases out of 371; 56%), a significant number of immigrant women also die in commuting accidents involving no vehicles (4%); Italian and immigrant men die mainly from causes related to the work environment (48%), especially immigrants (54%), and not from commuting accidents (921 out of 3997; 23%). Prevalent age at commuting fatality is 35-49 years, and among immigrant women 18-34. Deaths among women occur mostly in Northeast Italy, and among women working in health and social services; among immigrant women accommodation and catering services are also relevant. The highest number of fatal accidents among men occurs in Northwest Italy, among men working in wholesale trade. All fatalities take place mainly going to work, between 5-10 a.m., among women from October to December, among men from July to September, among Italian women are significantly higher on Saturday, among immigrant women on Sunday. Deaths among men are significantly higher in the eighth hour of work, between 3- 8 p.m. and on Monday among Italian workers, on Wednesday among immigrant men. Conclusions: Commuting fatalities among women, according to INAIL Statistical Data, show specific risk conditions by age, immigration, work activity, geographical area, working time, month and day of the week that require targeted preventive policies.